(untitled) (Open International Journal of Informatics, 2022)
This study adopted the UTAUT2 model to investigate the moderating impact of gender and level of education differences that influence the intention and use of social networking sites (SNS) among students at higher learning institutions in Malaysia. Specifically, the researchers were interested in determining whether or not gender and education level played a role in this relationship. A total of 498 students participated in the online survey to evaluate the SNS’s acceptance. Partial Least Square Multigroup Analysis (PLS-MGA) revealed that gender moderated the relationship between Technology Cluster and SNS Use Behavior. Additionally, education levels moderated the relationship between Facilitating Conditions and SNS Use Behavior and, between Habit and SNS Use Behavior. These findings provided helpful information for social networking service providers or educational institutions to better understand students’ behaviour toward using social networking services. This enabled the stakeholders to improve the features of social networking services or maximise the use of SNS in accordance with the findings.